Diagnosis of critical congenital heart defects in Iceland 2000-2014 - Kristinsdóttir, Hallfríður; Þórkelsson, Þórður; Harðardóttir, Hildur; Óskarsson, Gylfi (Journal of Cardiology and Cardiovascular Medicine, 2019)
Critical congenital heart defects (CCHDs) are preferably diagnosed prenatally or soon after birth. Late diagnosis has been related to poorer prognosis. The aim of this study is to assess when CCHDs are diagnosed in Iceland and whether late diagnosis is a problem. All live born children in Iceland and foetuses diagnosed with CCHDs during the years 2000-2014 were included. CCHD was defined as a defect requiring intervention or causing death in the first year of life, or leading to abortion. The total number of pre- and postnatal diagnosis of CCHDs was 188. Prenatal diagnosis was made in 69 of 188 (36.7%). Of 69 diagnosed prenatally 33 were terminated due to CCHD. Of the 155 live born children with CCHD, 36 (23.2%) had a prenatal diagnosis and 100 (64.5%) were diagnosed shortly after birth, before discharge from birth facility. 19 children (12.3%) were diagnosed late, that is after discharge from birth facility. Coarctation of the aorta was the most common CCHD diagnosed late (6/19). Prenatal screening and newborn examination give good results in diagnosis of CCHDs in Iceland. Late diagnosis are relatively few, but both the number of prenatally diagnosed CCHDs and CCHDs diagnosed shortly after birth can be further improved.